Resilience and Computer Addiction of Adolescents with Musculoskeletal Disorders - Lyubov Bazaleva; Victoria Erdakova; Yulia. E. Makarevskaya; Yulia. V. Sycheva (ARPHA Proceedings, 2022)
Adolescents with musculoskeletal disorders are reported to experience difficulties in building relationships with peers, poorly adapt in a team, which contributes to their escape from life's difficulties into the virtual world and the gradual formation of computer addiction. With computer addiction, a child may have increased irritability, a tendency to illegal actions, which leads to a hostile perception of the surrounding social world. Their ability to express their thoughts, establish contacts and dialogues with other people in real life suffers. Against the background of social maladjustment with excessive enthusiasm for games, some schoolchildren develop unjustified aggression, cruelty; most of them do not know how to productively overcome difficulties. The purpose of the research is to identify the characteristics of resilience in adolescents with musculoskeletal disorders with different levels of computer addiction. The following diagnostic methods were used in the study: S. Maddi's Hardiness Survey (adapted by D. A. Leontiev, E. I. Rasskazova), Internet addiction test (T. A. Nikitina, A. Yu. Egorov). The sample comprised 30 participants. The data was analyzed using the methods of mathematical data processing (nonparametric statistical Kruskal-Wallis test, Spearman’s rank correlation coefficient). Research results showed that adolescents with musculoskeletal disorders are characterized by a lower level of resilience. They are willing to show more passive behavior and avoid stressful situations.